2011
DOI: 10.1016/j.ijgo.2011.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Fertility and pregnancy outcomes among women with obstetric fistula in rural Malawi

Abstract: Even 2 years after undergoing surgical repair, women can continue to experience the effects of obstetric fistula, which include infertility, spontaneous abortion, and perinatal mortality. The factors responsible for extensive infertility and poor pregnancy outcome in women post-repair warrant further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 11 publications
0
37
1
Order By: Relevance
“…Our scoping review on pregnancy and childbirth post‐repair of an obstetric fistula in sub‐Saharan Africa found that many women still desire to become pregnant after the repair of their OF . However, the incidence of pregnancies was not reported in the reviewed studies, and the overall incidence could not be estimated in this review.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Our scoping review on pregnancy and childbirth post‐repair of an obstetric fistula in sub‐Saharan Africa found that many women still desire to become pregnant after the repair of their OF . However, the incidence of pregnancies was not reported in the reviewed studies, and the overall incidence could not be estimated in this review.…”
Section: Discussionmentioning
confidence: 87%
“…The 16 studies that met our inclusion criteria were published between 1978 and 2016, mostly in the past 10 years. Studies were conducted in only seven sub‐Saharan African countries: five in Nigeria , four in Ethiopia , two in Malawi , one in Niger , one in Mali , one in both Mali and Niger , one in Sierra Leone and one in Eritrea (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been widely reported that women who experience obstetric fistulas are often abandoned not only by their husbands, but also by their relatives and friends [6, 10, 29]. Consequently, they are left to deal with the huge responsibilities of the family and children alone [6].…”
Section: Discussionmentioning
confidence: 99%
“…Wilson et al [36] noted, 'Although surgical repair can resolve physical problems associated with birth injury, personal problems (e.g., marital relations, sexual health, mental health, infertility, and childbearing complications) seem to persist postrepair' [p. 198]. Wilson et al [36] noted, 'Although surgical repair can resolve physical problems associated with birth injury, personal problems (e.g., marital relations, sexual health, mental health, infertility, and childbearing complications) seem to persist postrepair' [p. 198].…”
Section: A Broad View Of Success: the Whole Womanmentioning
confidence: 99%